Effects of high-temperature thermal annealing on GeSn thin-film material and photodetector operating at 2 µm - Wu, Shaoteng (2021)
Here, we explore the thermal stability of GeSn epilayers with varying Sn contents (3-10%) at an annealing temperature ranging from 300 to 750°C. It is found that ordered nanopatterns are formed on the surface of GeSn with Sn content of 8% without excessive Sn precipitation after thermal annealing at 700°C. Despite being annealed at high temperatures, the GeSn maintains its crystal structure, which is confirmed by the X-ray Diffraction (XRD), Raman spectrum, and secondary-ion mass spectrometry (SIMS). The corresponding photocurrents of the photodetectors at the wavelength of 2 µm also indicate the crystal quality of the GeSn alloys does not deteriorate significantly after high-temperature annealing (675-700°C). Meanwhile, the decrease of dark current with the enhancement of Ip/Id ratio (on-off ratio) indicates the improvement of detectivity of the photodetector due to the annealing process. Furthermore, the annealing temperature is optimized to 550°C to achieve 200% enhancement of photocurrents of the GeSn photodetectors operated at 2 µm.